SOCIAL PROTECTION OF THE RIGHTS OF ORPHANS AND CHILDREN LEFT WITHOUT PARENTAL CARE: INTERNATIONAL LEGAL STANDARDS AND NATIONAL ASPECTS - Bekbutaeva, Lobar (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article explores international legal standards and national frameworks for protecting the rights of orphans and children deprived of parental care. It examines key international documents, including the UN Convention on the Rights of the Child and the Guidelines for the Alternative Care of Children, highlighting their impact on the development of national legal systems. Focusing on Uzbekistan, the article analyzes legislative acts such as the updated Constitution (2023), the Family Code, and the Law "On Guarantees of the Rights of the Child." The author underscores the country’s progress in child social protection while identifying persistent challenges, such as resource constraints, workforce shortages, and gaps in monitoring legislative implementation. The article proposes measures to strengthen the child protection system, emphasizing enhanced interagency collaboration, greater transparency in government operations, and the active participation of civil society.